The role of psychogenic factors in the etiopathogenesis of autoimmune disorders in the oral cavity - Nadya T. Avramova; Boyko K. Bonev (Journal of Mind and Medical Sciences)
Autoimmune disorders (AD) represent a heterogeneous group of multifactorial chronic conditions, which are triggered secondary to the loss of self-antigen tolerance. Their etiology involves genetic, epigenetic, and environmental factors; however, AD cannot be explained by these factors alone. Recent studies have shown increasing stress levels in industrialized countries and also increasing trends in the prevalence of autoimmune diseases. The oral mucosa is extremely responsive to emotional influences such as stress, anxiety and depression. Therefore, oral diseases can appear as a direct expression of emotions or indirectly, due to various psychological mechanisms. The aim of this study is to find and present possible correlations in order to support the hypothesis that psychogenic factors can play a significant role in the etiopathogenesis of autoimmune disorders in the oral cavity. The review is focused on clarifying epidemiology, etiology, pathogenesis, course, clinical signs, and management of oral lichen planus, recurrent aphthous stomatitis, psoriasis, muco-membranous pemphigoid, pemphigus, and erythema multiforme. Existing literature suggests bidirectional links between psychogenic factors and autoimmune diseases, which influence patients' psychological well-being and quality of life. Consequently, research and medical practice must continue investigations related to the proper diagnosis and clinical management of these conditions. The first signs of several diseases first appear in the oral cavity, which means that dentists can play an important role in the early diagnosis and treatment of AD oral. Although the role of psychological factors in the etiopathogenesis of AD is still underestimated, a holistic multidisciplinary approach should be implemented to provide for these health problems an appropriate diagnostic and therapeutic procedures.